PERANAN LABORATORIUM PENDIDIKAN PANCASILA DALAM MENGEMBANGKAN CIVIC COMPETENCES PESERTA DIDIK - Lutfiana, Rose Fitria (2014)
Penelitian ini didasari fakta bahwa belum ada sekolah dari jenjang pendidikan dasar sampai pendidikan atas yang mengembangkan laboratorium IPS atau laboratorium PKn atau Laboratorium Pendidikan Pancasila dalam menunjang tuntutan paradigm baru PKn dan kurikulum 2013 yaitu civic competences atau kompetensi kewarganageraan (civic knowledge, civic skills dan civic disposition) yang harus diajarkan kepada peserta didik secara seimbang. Tujuan dalam penelitian ini antara lain mengkaji dan memperoleh data, fakta dan informasi argumentatif tentang Laboratorium Pendidikan Pancasila SMP Negeri 1 Bantul dalam mengembangkan Civic Competences peserta didik. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Subyek penelitian antara lain kepala sekolah, kepala Laboratorium Pendidikan Pancasila, guru PKn, peserta didik SMPN 1 Bantul dan Bapak Bambang Edy S.Teknik pengumpulan data menggunakan wawancara, observasi dan studi dokumentasi. Teknik analisis data dalam penelitian ini yaitu pengumpulan data, reduksi data, display data dan simpulan. Hasil penelitian ini menunjukkan: (1) Laboratorium Pendidikan Pancasila SMP Negeri 1 Bantul memiliki peranan dalam mengembangkan civic competences atau kompetensi kewarganegaraan peserta didik; (2) Civic knowledge peserta didik meliputi pemahaman dalam materi pemerintahan, politik, hak dan kewajiban warganegara, dan demokrasi; (3) Civic skills peserta didik meliputi kemampuan intelektual dan kemampuan partisipasi yang terlihat dalam proses diskusi, presentasi dan Tanya jawab; (4) Civic disposition peserta didik meliputi religius, jujur, tanggung jawab, disiplin, kritis dan toleransi. Laboratorium Pendidikan Pancasila berperan penting dalam mengembangkan civic competences peserta didik, oleh karena itu Laboratorium Pendidikan Pancasila perlu dioptimalkan pemanfaatannya dan dikembangkan oleh sekolah lain. Kata Kunci: LaboratoriumPendidikanPancasila, Civic Competences The new paradigm of civics and curriculum 2013 requiring the facilitation of laboratory to develope civic competences. The existence of laboratory of civic in schools assumed being significant media as learning innovations to reach it. But, the problem is in Indonesia so far very rarely founded the civic laboratories at all levels of education. In time, SMPN 1 Bantul Yogyakarta become the first yunior high school that have the laboratory of Pancasila education. I assumed that the laboratory of pancasila in SMPN 1 Bantul playing the urgent role to develope civics competences of students including civic knowledges, civic skills and civic dispositions. But, how the role playing is to be questionable. Based on that back ground, this study try to find out how the role of laboratory of pancasila education in SMP N 1 Bantul in developing civic competences of students? The purpose of this research is to study and acquire the descriptions about the Laboratory of Pancasila in SMPN 1 Bantul in developing the civic competences of students. This research is using a qualitative approach with descriptive method. The subjects in this study were principals, chief of the education of Pancasila, Civic teachers and students in SMPN 1 Bantul. To collecting data, this research using interviews, observation and documentation study. The technique of data analysis in this study is using data collection, data reduction, data display and conclusion.The result of this research showed that: (1) the Laboratory of Pancasila Education in SMPN 1 Bantul have roles in developing citizenship of civic competences or the competence of students; (2) the civic knowledges includes the students understanding both in terms of governance, politics, rights and obligations of citizens, and democracy; (3) The civic skills of students include the intellectual ability and the cability of the visible participation in the process of discussions and presentations; (4) The civic disposition of students is pretty good. This is seems from some of the characters as like, honesty, responsibility, discipline, which looks at the students themselves. The laboratory of Pancasila education was instrumental facilitation in developing the civic competences of students. Therefore, the utilizations of Pancasila Education Laboratory needs to be optimized and developed by other schools. Keywords: The Laboratory of Pancasila Education, Civic Competences.